Intellectual Property Design with PUF-based Hardware Security - Podugu, Devi Pradeep; Kamala Kumari, A.; Sabbavarapu, Srinivas (Engineering, Technology & Applied Science Research, 2024)
With the advent of networked systems in almost all current applications, security poses a great threat to the design industry. The participation of several people in different design abstract stages in the hierarchical design industry makes the design vulnerable to security threats. To address these security issues, this study used PUFs to create signatures on Intellectual Property (IP) to protect against malicious attacks. The proposed method exhibits significant resilience to ML-based attacks.